Strategi Dinas Kebudayaan dan Pariwisata Dalam Promosi Tempat Wisata di Kota Palangka Raya - Muhamad Yusuf; Andry Febri Pratama (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2018)
This research aims to know and analyze the strategy of the Culture and Tourism office in promoting the place/tourism products to the public and tourists. Also, to find out what are the obstacles to promoting tourist attractions in the city of Palangka Raya. This research uses qualitative research, which is the instrument is the researcher himself to be able to become instruments then the researcher must have a wide provision of theory and insight, to be able to ask, analyze, photograph, and To contract objects that are meticulously clearer and meaningful. In qualitative research, data collection is not in the theory of the Guide but guided by the facts found at the time of research in the field. Based on the results of data analysis can be explained that the strategy that should be done in the marketing of tourism promotion is to make the event such as showing the regional peculiarities, cultural exhibitions, river ship parade. Things like that will attract tourists to stay how packing the attraction and its promotion. Such activities can be done in the middle of the city center so that people and tourists easily reach the location, in addition it should also package products that have the value of cultural selling, price according to facilities, and most importantly prepare a place The Tour's flagship is truly mature in terms of infrastructure, facilities, and infrastructure. For government and Tourism service drivers in terms of strategy in the promotion is the supporting power needs to be improved again so that our beautiful city is known in other regions, because it is in the world when the city is immersed in its tourism, but A myriad of historical, Acirianalam, and the tranquility of the city.